An in vivo expression system for the identification of cargo proteins of vacuolar sorting receptors in Arabidopsis culture cells. (19th July 2013) - Shen, Jinbo; Suen, Pui Kit; Wang, Xiangfeng; Lin, Youshun; Lo, Sze Wan; Rojo, Enrique; Jiang, Liwen
Summary Vacuolar sorting receptors (VSRs) are type I integral membrane family proteins that in plant cells are thought to recognize cargo proteins at the late Golgi or trans‐Golgi network (TGN) for vacuolar transport via the pre‐vacuolar compartment (PVC). However, little is known about VSR cargo proteins in plants. Here we developed and tested an in vivo expression system for the identification of VSR cargos which is based on the premise that the expressed N‐terminus of VSRs will be secreted into the culture medium along with their corresponding cargo proteins. Indeed, transgenic Arabidopsis culture cell lines expressing VSR N‐terminal binding domains (VSRNTs) were shown to secrete truncated VSRs (BP80NT, AtVSR1NT and AtVSR4NT) with attached cargo molecules into the culture medium. Putative cargo proteins were identified through mass spectrometry. Several identified cargo proteins were confirmed by localization studies and interaction analysis with VSRs. The screening strategy described here should be applicable to all VSRs and will help identify and study cargo proteins for individual VSR proteins. This method should be useful for both cargo identification and protein–protein interaction in vivo.